TURTLE GEOMETRY IN EDUCATION - LAVRINCIK, Jan; Milan, KLEMENT (Trends in education, 2010)
The article deals with the significance creation, classification, and use recursion algorithms in education, especially turtle geometry. The origins of the parts are explained, notion recursion algorithms, and use in the contemporary time are remembered. The choice of recursion algorithms is emphasized from the field of expert demands and expansion of abstract thinking in pupils the lower secondary school. It pontificate readers with plus and minus common algorithms. At the end, it discusses about the future use of Microsoft Visual Basic 6 in the lower secondary education and potential usage in program RVP.
Keywords: algorithm; recursion algorithm; Visual Basic; turtle graphic.